2020
DOI: 10.1101/2020.03.05.978528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Essential roles for deubiquitination inLeishmanialife cycle progression

Abstract: 14 The parasitic protozoan Leishmania requires proteasomal, autophagic and lysosomal 15 proteolytic pathways to enact the extensive cellular remodelling that occurs during its life cycle.16 The proteasome is essential for parasite proliferation, yet little is known about the requirement 17 for ubiquitination/deubiquitination processes in growth and differentiation. Activity-based 18 protein profiling of L. mexicana C12, C19 and C65 deubiquitinating cysteine peptidases 19 (DUBs) revealed DUB activity remains re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Previous work has underscored the importance of the ubiquitination system in Leishmania by demonstrating both the essentiality of the parasite proteasome and a key role for DUBs in the life cycle of this parasite (8,15). Our generation of a select ubiquitination gene null mutant library revealed that 1 out of 2 ubiquitin E1s and 4 out of 13 ubiquitin E2s could not be deleted and therefore may be essential in promastigotes.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous work has underscored the importance of the ubiquitination system in Leishmania by demonstrating both the essentiality of the parasite proteasome and a key role for DUBs in the life cycle of this parasite (8,15). Our generation of a select ubiquitination gene null mutant library revealed that 1 out of 2 ubiquitin E1s and 4 out of 13 ubiquitin E2s could not be deleted and therefore may be essential in promastigotes.…”
Section: Discussionmentioning
confidence: 87%
“…Our generation of a select ubiquitination gene null mutant library revealed that 1 out of 2 ubiquitin E1s and 4 out of 13 ubiquitin E2s could not be deleted and therefore may be essential in promastigotes. A smaller proportion (4 out of 20) cysteine peptidase DUBs were shown to be essential in promastigotes, perhaps due to a greater degree of redundancy in DUB function (8). UBC12, a putative Nedd8 E2, also appears to be essential in promastigotes, suggesting it functions independently of the Nedd8 E1 UBA3, which is non-essential in promastigotes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations